Russian geomagnetic recordings in 1850–1862 compared to modern observations - Viljanen Ari; Myllys Minna; Nevanlinna Heikki (Journal of Space Weather and Space Climate, 2014)
We analyse geomagnetic recordings at four subauroral and midlatitude Russian observatories in 1850–1862. The data consist of spot readings made once in hour of the north and east components of the magnetic field. We use the hourly change of the horizontal field vector as the measure of activity. We compare these values to data from modern observatories at corresponding magnetic latitudes (Nurmijärvi, Finland, magnetic latitude ~57 N; Tartu, Estonia, ~54.5 N; Dourbes, Belgium, ~46 N) by reducing their data to the 1-h format. The largest variations at the Russian observatories occurred during the Carrington storm in September 1859 and they reached about 1000 nT/h, which was the instrumental off-scale limit. When the time stamp for the spot readings happens to be optimal, the top variation in the Nurmijärvi data is about 3700 nT/h (July 1982), and at Tartu the maximum is about 1600 nT/h (November 2004). At a midlatitude site Nertchinsk in Russia (magnetic latitude ~45 N), the variation during the Carrington storm was at the off-scale limit, and exceeded the value observed at Dourbes during the Halloween storm in October 2003. At Nertchinsk, the Carrington event was at least four times larger than any other storm in 1850–1862. Despite the limitations of the old recordings and in using only hourly spot readings, the Carrington storm was definitely a very large event at midlatitudes. At higher latitudes, it remains somewhat unclear whether it exceeds the largest modern storms, especially the one in July 1982.